1997
DOI: 10.2494/photopolymer.10.175
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Semiconducting Polymer Films by High Intensity Photo-Chemical Processes with Excimer Laser Beams.

Abstract: Excimer laser ablation (ELA) of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), 3,4,9,10-perylenetetracarboxylic diimide (PTCDI), 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTCDA) and perylene with 193(ArF), 248(KrF) and 308nni(XeCI) beams results in formation of amorphous semiconducting polymer thin films consisting of fine particles on several temperature-controlled substrates. The structure and electric conductivity of each prepared film depend considerably on the target material, ablation wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In recent years, particularly, preparation of PPN films by laser ablation has been attracted a great deal of attention. [5][6][7] In our previous paper [6,7], we found that excimer laser ablation ( prepared on substrates at 300°C by ELA at various fluences, structure of the nano-particles depended strongly on fluence. While the peak at 1296 cm' due to in-plane C-H bending remained in each nano-particles prepared at less than 0.5 Jcm2pulse1, it disappeared and the spectrum turned into that of common amorphous carbon with a peak at 1600cm1 and broad band around 1400 cm1 for each film prepared at more than 1.0…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, particularly, preparation of PPN films by laser ablation has been attracted a great deal of attention. [5][6][7] In our previous paper [6,7], we found that excimer laser ablation ( prepared on substrates at 300°C by ELA at various fluences, structure of the nano-particles depended strongly on fluence. While the peak at 1296 cm' due to in-plane C-H bending remained in each nano-particles prepared at less than 0.5 Jcm2pulse1, it disappeared and the spectrum turned into that of common amorphous carbon with a peak at 1600cm1 and broad band around 1400 cm1 for each film prepared at more than 1.0…”
Section: Introductionmentioning
confidence: 98%
“…These carbon-based compounds have been synthesized by the pyrolysis of various organic compounds, including polymers, such as polyimide and p-conjugated low-molecularweight compounds, using heat sources such as electric furnaces [4][5][6][7][8][9][10] and lasers. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Among these sources, laser is an attractive heat source because it has advantages that other heat sources do not possess. For example, laser enables a target to be heated rapidly to a very high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical change allows the preparation of promising functional organic films with unique structures different from the original target materials. 1,2 The other purpose is thin film preparation with accurate structure transfer from the target of various polymers and of some nonpolymeric compounds. It has been known that the PLD technique enables preparation of thin films with similar structure as the target from organic polymers that are difficult to process, such as polytetrafluoroethylene ͑PTFE͒.…”
Section: Introductionmentioning
confidence: 99%